High-mechanical-property biphasic amphiphilic gel based on myofibrillar protein and pepper essential oil as well as preparation method and application of high-mechanical-property biphasic amphiphilic gel

Preparation of biphasic amphiphilic gel through myofibrillar protein and pepper essential oil solves the problem of high-calorie and high-fat foods, and realizes low-calorie and low-fat fat substitutes, with excellent mechanical properties and storage stability. Food alternatives with high nutritional value.

CN119302427APending Publication Date: 2025-01-14ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411704625.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The eating habits of high-calorie and high-fat in existing foods lead to health problems, and traditional fat substitutes such as oil gels have high fat content and poor mechanical properties of hydrogels, making it difficult to meet the needs of high nutritional and good texture.

Method used

A high mechanical performance biphasic amphiphilic gel is prepared using myofibrillar protein and pepper essential oil. By extracting myofibrillar protein, preparing pepper essential oil gel and myofibrillar hydrogel, and combining it to form a biphasic coagulation. Gel structure is constructed through high-pressure homogenization and heat-induced processes.

Benefits of technology

It has achieved low-calorie, low-fat fat substitutes, with excellent mechanical properties and good storage stability, and can be used as a food substitute with high nutritional value, significantly improving the maximum stress and Young's modulus of the gel, maintaining the The internal structure and uniformity of the oil gel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119302427A_ABST
    Figure CN119302427A_ABST
Patent Text Reader

Abstract

The invention relates to the field of food processing, and particularly discloses a high-mechanical-property biphasic amphiphilic gel based on myofibrillar protein and pepper essential oil as well as a preparation method and application of the high-mechanical-property biphasic amphiphilic gel. Myofibrillar protein hydrogel is prepared through thermal induction, beeswax oil gel containing pepper essential oil is prepared through magnetic oscillation self-assembly, and the high-mechanical-property biphasic amphiphilic gel containing pepper essential oil is prepared through magnetic oscillation self-assembly. And preparing the two-phase amphiphilic gel simultaneously containing a water phase and an oil phase through high-speed homogenization and thermal induction. The mechanical property, thermal stability and structure of the two-phase amphiphilic gel with different oleogel to hydrogel ratios are evaluated by adopting mechanical property, thermal property, binding capacity and microstructure analysis methods and the like. Experiments confirm that the prepared biphasic amphiphilic gel can be used as a substitute of traditional fat, can be used for embedding and delivering probiotics or active ingredients and the like, and can be used for personalized customization of food or precise nutrition realization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food processing, and more specifically, relates to a high-mechanical-performance biphasic amphiphilic gel prepared from myofibrillar protein and prickly ash essential oil and its application in food processing. Background Art

[0002] Urbanization and busy lifestyles have shifted people's diet and lifestyle habits toward high-calorie and high-fat density food intake and sedentary behavior. Excessive intake of saturated fatty acids and trans fats leads to an increased risk of diet-related diseases such as type 2 diabetes, metabolic syndrome, and obesity. Therefore, it is necessary to find fat-like substitutes that can improve the nutritional quality of products and meet people's health needs while meeting food processing characteristics and plasticity.

[0003] Oleogel solidifies by fixing liquid oil in a three-dimensional network formed by gelling agents and stabilizers, and can be used as a substitute for solid fat, but the fat content is as high as 90%, which still leads to high fat intake. Hydrogel is formed by a class of highly hydrophilic polysaccharides, proteins and other substances through water adsorption and coagulation, but the hydrogel formed by natural polymers has poor mechanical properties and adjustable properties. Biphasic amphiphilic gel is a new type of biphasic system produced by oleogel and hydrogel at a specific temperature and shear rate, showing a unique amphiphilic semi-solid state. Biphasic amphiphilic gel combines the advantages of oleogel and hydrogel, and has excellent physicochemical stability, unique rheological properties and controlled release properties. The biphasic amphiphilic gel system is a crystalline network that simulates the properties of solid fat, and it does not perform any chemical or structural modification on the triglycerides in the oil phase. The performance of biphasic amphiphilic gel is closely related to the oil-water ratio, the type and concentration of the gelling agent, and the preparation method.

[0004] As an important source of amino acids, myofibrillar protein has good biocompatibility, but its solubility and stability limit its application in increasing the nutritional value of food and improving the taste and texture of food. Myofibrillar protein can be used as a gelling agent for the preparation of hydrogels. Zanthoxylum bungeanum essential oil is the main component of the aroma of Zanthoxylum bungeanum. Its strong numbing and spicy aroma can significantly enhance the flavor and taste of food, increase appetite, and has good antibacterial and antioxidant effects. It can be used for food preservation and preservation, and prolong the shelf life of food, but the role of Zanthoxylum bungeanum essential oil in oil gel is still limited. Therefore, it is very necessary to establish a biphasic amphiphilic gel with high nutritional value, strong mechanical properties and flavor retention characteristics. It can not only replace traditional solid fats, but also show great potential in improving the nutritional value of new foods or personalized foods and delivering bioactive substances. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention develops a biphasic amphiphilic gel system with excellent mechanical properties and low calorie and low fat functions based on myofibrillar protein and Zanthoxylum bungeanum essential oil. It has been verified that the system is feasible as a fat substitute and can be used to further develop fat substitute foods with high nutritional value and good texture and taste.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a biphasic amphiphilic gel with high mechanical properties based on myofibrillar protein and Zanthoxylum bungeanum essential oil comprises the following steps:

[0008] (1) Extraction of myofibrillar protein: Cut fresh pork into small pieces and mash them, mix them with 4 volumes of phosphate buffer (pH 7.0), homogenize them at 10,000-12,000 r / min for 1 min, filter them, centrifuge them at 2,000-5,000 r / min for 10 min, collect the precipitate to obtain crude myofibrillar protein, repeat this process twice, disperse the crude myofibrillar protein in 4 volumes of 0.1 M NaCl, homogenize them at 10,000-12,000 r / min for 1 min, centrifuge them at 2,000-5,000 r / min for 10 min, repeat this process twice, and obtain purified myofibrillar protein.

[0009] (2) Preparing an oil gel containing Zanthoxylum essential oil: adding Zanthoxylum essential oil to corn germ oil, and then adding an oil gelling agent, beeswax, to the corn germ oil containing Zanthoxylum essential oil to obtain a mixture after magnetic stirring, and magnetically stirring and heating the mixture to dissolve the oil gelling agent, cooling, and storing for a period of time to allow the oil gel to be completely formed.

[0010] (3) Preparation of myofibrillar protein hydrogel: The preparation method of myofibrillar protein hydrogel in step (3) is as follows: disperse the myofibrillar protein obtained in step (1) into phosphate buffer to a concentration of 40-60 mg / mL, homogenize at 10000-12000 r / min for 40-80 s, centrifuge at 3000-4000 r / min for 3-5 min, equilibrate at room temperature for 20-40 min, equilibrate in a water bath at 80-85°C for 30-40 min, and immediately cool to obtain myofibrillar protein hydrogel, which is stored at 4°C, wherein the water bath heating rate is 1-2°C / min.

[0011] (4) Preparing a two-phase amphiphilic gel: heating and solubilizing the oil gel prepared in step (2), cooling it, and then mixing it with the myofibrillar protein hydrogel prepared in step (3). After homogenization, placing it in a cylindrical mold, heating it in a water bath, cooling it in an ice water bath, and storing it at 4° C. to obtain a two-phase amphiphilic gel.

[0012] Furthermore, in step (2), the concentration of the pepper essential oil in the corn germ oil is 0.2-0.4%, and the concentration of the oil gelling agent beeswax in the corn germ oil containing the pepper essential oil is 8-12%, and the concentration unit is g / mL.

[0013] Furthermore, in step (2), the magnetic stirring speed is 300-500 r / min, and the magnetic stirring time is 30-60 min; the heating temperature is 130-145° C., the storage temperature is 23-27° C., and the storage time is 24 h.

[0014] Furthermore, in step 4), the solubilization temperature is 70-80°C, the oil gel cooling temperature is 60-65°C, the volume ratio of the oil gel to the hydrogel is (70-90):(10-30), the homogenization speed is 10000-12000r / min, the homogenization time is 40-60s, the water bath temperature is 80-85°C, the water bath heating time is 30-40min, the water bath heating temperature rise rate is 1-2°C / min, and the ice water bath cooling time is 30-35min.

[0015] The invention also provides a two-phase amphiphilic gel prepared by the preparation method.

[0016] The present invention also provides the use of the two-phase amphiphilic gel prepared by the above preparation method in fat substitutes, and the feasibility of using the two-phase amphiphilic gel as a fat substitute is evaluated. The application potential of the two-phase amphiphilic gel as a fat substitute in food is evaluated by optical microscopy, confocal laser scanning microscopy (CLSM), Fourier transform infrared spectroscopy (FTIR), texture analysis, differential scanning calorimetry (DSC), X-ray diffraction (XRD), sensory analysis and storage stability evaluation.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention uses myofibrillar protein with good biocompatibility and high nutritional value, and prickly ash essential oil with appetite enhancement, freshness preservation and antibacterial properties to prepare a two-phase amphiphilic gel. The gel system has excellent mechanical properties and low calorie and low fat functions. It has been verified that the system is feasible as a new fat substitute, and it has a promising prospect as a fat substitute in the production of high nutritional value and good texture and taste foods, and can be applied to food processing and nutrition and health industries.

[0019] The present invention uses a two-phase amphiphilic gel preparation process constructed by high-pressure homogenization combined with thermal induction to achieve good storage stability of the mixed gel. It has been verified that the gel is stored at 4°C for 60 days without separation of the oil phase and the water phase, and the water-oil binding force is as high as 82.25% or more. From the appearance, the color of the two-phase amphiphilic gel prepared in the present invention is similar to that of the oil gel, which is creamy yellow; the test tube inversion experiment shows that there is no liquid flow, indicating that the self-supporting structure of the gel formed by the interweaving of the hydrogel and the oil gel is stable. The rheological properties test results show that the gel has obvious solid-like elastic characteristics, and the gel can resist high-frequency scanning in the linear viscoelastic region and maintain good viscoelasticity and strength. The presence of myofibrillar protein hydrogel enhances the nutritional properties of the oil gel. 70% of the oil gel increases the maximum stress of the two-phase gel by 5.46 times and the Young's modulus by 3.15 times, which significantly improves the mechanical properties of the hydrogel. In addition, the addition of Zanthoxylum bungeanum essential oil greatly adjusted the mechanical properties of the oil gel. The maximum stress in the 70:30 formula with added Zanthoxylum bungeanum essential oil (Example 1) was 170.15 g, which was significantly less than 274.45 g without adding Zanthoxylum bungeanum essential oil (Comparative Example 1). It can be seen that under the premise of ensuring the protein content, the addition of trace amounts of Zanthoxylum bungeanum essential oil can significantly adjust the mechanical properties of the two-phase gel, and solid gels with adjustable mechanical properties can be produced according to demand.

[0020] The results of spectral analysis and structural characterization show that the biphasic amphiphilic gel is formed by the physical interaction between the hydrogel and the oil gel, without changing its original chemical properties, and the gel structure is tight and the water and oil are evenly distributed. It can be seen that the biphasic amphiphilic gel maintains the tight internal structure and good uniformity of the oil gel while enhancing the mechanical properties and nutritional properties, and has good storage stability. It has the potential to become a traditional fat substitute with high nutritional value, and can also be used in the field of separate or simultaneous delivery of fat-soluble and water-soluble functional factors. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 It is a visual diagram of hydrogel (A), beeswax oil gel containing pepper essential oil (B), two-phase amphiphilic gel (70:30, C) and (90:10, D);

[0023] Figure 2 The maximum stress diagrams are for hydrogel, beeswax gel containing Zanthoxylum essential oil, and two-phase amphiphilic gel (70:30) and (90:10);

[0024] Figure 3 Young's modulus diagram of hydrogel, oil gel, and two-phase amphiphilic gel;

[0025] Figure 4 It is the binding force of hydrogel, oil gel and two-phase amphiphilic gel;

[0026] Figure 5 It is the water distribution diagram of hydrogel and two-phase amphiphilic gel;

[0027] Figure 6 Thermal performance analysis diagrams of hydrogel, oil gel and two-phase amphiphilic gel;

[0028] Figure 7 FT-IR analysis of hydrogel, oil gel and two-phase amphiphilic gel;

[0029] Figure 8 XRD patterns of hydrogel, oil gel and two-phase amphiphilic gel;

[0030] Fig. 9 SEM and CLSM gel microstructure images of the two-phase amphiphilic gel.

[0031] Fig.10 Storage modulus (G′) and loss modulus (G″) of biphasic amphiphilic gels at a frequency sweep of 1–100 Hz.

[0032] Fig.11 Figure 3. Changes in binding force of hydrogels and biphasic amphiphilic gels during storage time of 1-60 days. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the following examples, the raw materials used are all common commercial products that can be directly purchased or can be prepared by referring to conventional methods in the art. If there are processes or experimental operations not mentioned in detail, conventional techniques in the art can be used.

[0035] Example 1

[0036] The preparation method of the high mechanical performance biphasic amphiphilic gel based on myofibrillar protein and Zanthoxylum bungeanum essential oil in this embodiment comprises the following steps:

[0037] Step 1: Extract myofibrillar protein

[0038] Cut fresh pork into 1cm×1cm small pieces and crush them in a tissue crusher. Mix with 4 volumes of phosphate buffer (pH 7.0) and homogenize at 12000r / min for 1min. Filter the meat slurry, centrifuge at 3000r / min for 10min, collect the precipitate, and obtain the crude myofibrillar protein precipitate. Repeat the above steps twice, then disperse the crude myofibrillar protein in 4 volumes of washing solution (0.1M NaCl), homogenize and centrifuge under the same conditions, repeat twice, and obtain purified myofibrillar protein. Determine the concentration of myofibrillar protein by the biuret method and store at 4℃ for use.

[0039] Step 2, preparation of oil gel containing Zanthoxylum bungeanum essential oil

[0040] Zanthoxylum bungeanum essential oil was added to corn germ oil at a concentration of 0.2% (w / v=g / mL), and magnetic stirring was carried out at 500r / min for 30min. Then, beeswax, an oil gel, was added to the corn germ oil containing Zanthoxylum bungeanum essential oil at a concentration of 10% (w / v=g / mL). The mixture was stirred (500r / min) and heated at 140°C for 30min to dissolve the oil gel, and then cooled to room temperature. The solution was stored at 25±2°C for 24h to allow the oil gel to be completely formed.

[0041] Step 3: Preparation of myofibrillar protein hydrogel

[0042] The myofibrillar protein from step 1 was dispersed in phosphate buffer to a concentration of 40 mg / mL, homogenized at a speed of 10000 r / min by a high-speed homogenizer for 1 min, and centrifuged at 3000 r / min for 5 min. After equilibration at room temperature for 30 min, the mixture was water bathed at 80°C for 30 min, and then immediately cooled to obtain a myofibrillar protein hydrogel, which was stored at 4°C.

[0043] Step 4: Preparation of two-phase amphiphilic gel

[0044] After heating and solubilizing the oil gel prepared in step 2 (70°C), the oil gel solution was cooled to 60°C and mixed with the myofibrillar protein hydrogel prepared in step 3 which was also heated to 60°C at a volume ratio of 70:30, and homogenized at 10000r / min for 1min. The mixture was placed in a cylindrical mold with a diameter of 22mm, heated in a water bath at 80°C for 30min, cooled in an ice water bath for 30min, and stored at 4°C to obtain a two-phase amphiphilic gel.

[0045] Example 2

[0046] In the preparation of the two-phase amphiphilic gel in step 4 of this embodiment, the volume ratio of the oil gel to the myofibrillar protein hydrogel is 90:10. The other steps are the same as those in embodiment 1.

[0047] Example 3

[0048] In the preparation of the two-phase amphiphilic gel in step 4 of this embodiment, the volume ratio of the oil gel to the myofibrillar protein hydrogel is 80:20. The other steps are the same as those in embodiment 1.

[0049] Comparative Example 1

[0050] The difference between the preparation method of the two-phase amphiphilic gel in this comparative example and that in Example 1 is that no pepper essential oil is added during the preparation of the oil gel. The specific preparation process is as follows:

[0051] Step 1: Extract myofibrillar protein

[0052] Cut fresh pork into 1cm×1cm small pieces and crush them in a tissue crusher. Mix with four times the volume of phosphate buffer (pH 7.0) and homogenize at 12000r / min for 1min. Filter the meat slurry, centrifuge at 3000r / min for 10min, collect the precipitate, and obtain the crude myofibrillar protein precipitate. Repeat the above steps twice, then disperse the crude myofibrillar protein in 4 times the volume of washing solution (0.1M NaCl), homogenize and centrifuge under the same conditions, repeat twice, and obtain purified myofibrillar protein. Determine the concentration of myofibrillar protein by the biuret method and store at 4℃ for use.

[0053] Step 2: Preparation of oil gel without Zanthoxylum bungeanum essential oil

[0054] The oleogel beeswax was added to corn germ oil containing Zanthoxylum essential oil at a concentration of 10% (w / v=g / mL). The mixture was stirred (500r / min) and heated at 140°C for 30min to dissolve the oleogel, then cooled to room temperature. The solution was stored at 25±2°C for 24h to allow the oleogel to form completely.

[0055] Step 3: Preparation of myofibrillar protein hydrogel

[0056] The myofibrillar protein from step 1 was dispersed in phosphate buffer to a concentration of 40 mg / mL, homogenized at a speed of 10000 r / min by a high-speed homogenizer for 1 min, and centrifuged at 3000 r / min for 5 min. After equilibration at room temperature for 30 min, the mixture was water bathed at 80°C for 30 min, and then immediately cooled to obtain a myofibrillar protein hydrogel, which was stored at 4°C.

[0057] Step 4: Preparation of two-phase amphiphilic gel

[0058] After heating and solubilizing the oil gel prepared in step 2 (70°C), the oil gel solution was cooled to 60°C and mixed with the myofibrillar protein hydrogel prepared in step 3 which was also heated to 60°C at a volume ratio of 70:30, and homogenized at 10000r / min for 1min. The mixture was placed in a cylindrical mold with a diameter of 22mm, heated in a water bath at 80°C for 30min, cooled in an ice water bath for 30min, and stored at 4°C to obtain a two-phase amphiphilic gel.

[0059] Comparative Example 2

[0060] The only difference between the preparation method of the two-phase amphiphilic gel in this comparative example and that in Example 2 is that no Zanthoxylum bungeanum essential oil is added during the preparation of the oil gel.

[0061] The myofibril hydrogel prepared in Examples 1 and 2, the beeswax gel containing pepper essential oil, the two-phase amphiphilic gel (70:30) and the two-phase amphiphilic gel (90:10) prepared in Example 2 are shown in FIG. Figure 1 From the appearance, under high-speed homogenization and heat induction, the oil gel and hydrogel phases can form a visually uniform semi-solid gel. As the oil gel ratio increases, the color of the two-phase amphiphilic gel changes from milky white to butter yellow, which is close to the color of the oil gel.

[0062] The myofibril hydrogel obtained in Example 1, the beeswax oil gel containing pepper essential oil, the two-phase amphiphilic gel (O:H=70:30), the two-phase amphiphilic gel prepared in Example 2 (O:H=90:10), the beeswax oil gel without pepper essential oil prepared in Comparative Example 1, the two-phase amphiphilic gel without pepper essential oil (O:H=70:30), and the two-phase amphiphilic gel without pepper essential oil prepared in Comparative Example 2 (O:H=90:10) were subjected to physical, chemical and structural analysis to evaluate their feasibility of replacing fat. The results are shown in Figure 2-8 .

[0063] 1. Mechanical properties analysis

[0064] Compression tests were performed using a TA-XT Plus texture analyzer with a cylindrical probe of 12 mm diameter at a pre-test speed of 1.00 mm / s and a post-test speed of 1.00 mm / s. The gels were compressed to 80% of their initial height and the mechanical properties of the hydrogels, oil gels, and two-phase amphiphilic gels were determined with a trigger force of 5.0 g. The maximum stress is shown in Figure 2 , Young's modulus see Figure 3 .

[0065] Depend on Figure 2It can be seen that after adding pepper essential oil, the hardness of the oil gel decreased significantly, and the maximum stress decreased from 1090.01g to 501.6g. With the increase of the oil gel component, the maximum stress of the two-phase amphiphilic gel increased, and the Young's modulus increased accordingly. The maximum stress increased from 50.23g of the hydrogel to 330.12g of the 90:10 formula, and increased to 257.41g for the formula containing pepper essential oil. The Young's modulus increased from 10505.37Pa of the hydrogel to 576882.36Pa of the 90:10 formula, and increased to 138675.21Pa for the formula containing pepper essential oil. For the same oil gel component, the maximum stress and Young's modulus of the two-phase amphiphilic gel containing pepper essential oil are significantly lower than those of the sample without pepper essential oil. For example, in the 70:30 formula, the maximum stress of the gel without pepper essential oil and the gel containing pepper essential oil are 274.11g and 170.15g, respectively, and the Young's modulus are 33118Pa and 16409.21Pa, respectively, indicating that pepper essential oil significantly affects the gel strength and maximum stress. The mechanical properties results show that changing the process parameters and gel composition can produce gel systems with different physical and chemical properties. Different mechanical properties will determine the application of the two-phase amphiphilic gel in the field of fat substitutes. Therefore, increasing the content of oil gel and hydrogel, adding chemical components such as essential oils, improving the mechanical properties of the two-phase amphiphilic gel, and adjusting the physical and chemical properties of the two-phase amphiphilic gel will increase the possibility of gel application.

[0066] 2. Combination ability

[0067] Place 1.5 g of the two-phase amphiphilic gel sample in a 2 mL Falcon tube and centrifuge at 8000 r / min for 15 min. Remove the excess liquid and weigh the Falcon tube and the remaining sample. Calculate the binding capacity. Figure 4 .

[0068] The results showed that the oil-water binding capacity of all two-phase amphiphilic gels was higher than 88.22%, among which the binding rates of 70:30 and 90:10 formulas without pepper essential oil were 88.22% and 94.36%, and the binding rates of 88.54% and 95.58% with pepper essential oil were significantly higher than the binding capacity of 66.42% of hydrogel. There was no significant difference in the binding rate of the two formulas of amphiphilic gels with or without pepper essential oil (p>0.05). This shows that the constructed two-phase gel system greatly improves the water-oil binding capacity of hydrogel. In addition, the binding capacity of the two-phase amphiphilic gel is positively correlated with the oil-gel ratio. The 90:10 two-phase amphiphilic gel has a strong structure and the highest binding capacity. The high-ratio oil gel matrix spontaneously forms a dense network structure. The addition of pepper essential oil did not reduce the binding capacity of the gel system. It can be seen that the addition of hydrogel and pepper essential oil significantly changed the mechanical properties of the gel system without reducing its water-oil binding capacity, reflecting the potential of the system as a fat substitute.

[0069] 3. Moisture distribution

[0070] The water distribution and relaxation time of the sample were measured using NMI20 low-field nuclear magnetic resonance. The test parameters were: proton resonance frequency of 18 MHz, cumulative scan times of 16 times, echo times of 15,000 times, relaxation waiting time of 4500 ms, and the results are shown in Figure 5 , relaxation times and peak area percentages are shown in Tables 1 and 2.

[0071] Table 1 T2 relaxation timetable of hydrogels and biphasic amphiphilic gels

[0072]

[0073] Table 2 Hydrogel and biphasic amphiphilic gel T2 peak area percentage table

[0074]

[0075] The results show that each gel sample has four peaks, and the water distribution in the two-phase amphiphilic gel is basically the same as that in the oil gel. 21 , T 22 and T 23 The relaxation time shifts to the left with the addition of oil gel, which is related to the enhanced oil-water interaction and is beneficial to retaining oil and water. 22 The relaxation time changes most significantly, moving from 208.46 ms of the hydrogel to 106.46 ms. 21 and T 22 The peak area percentage of bound water increases with the increase of oil gel content, among which T 22 The area percentage increased from 86.45% for the hydrogel to 95.98% for the 90:10 formulation. 23 The content was significantly reduced, T 23 The percentage decreased from 11.17% in the hydrogel to 1.23% in the 90:10 formula. There was no significant difference in the relaxation time and content of water molecules in the two-phase gel after the addition of pepper essential oil (p>0.05), indicating that the addition of pepper essential oil can improve the mechanical properties and flavor of the two-phase amphiphilic gel without significantly affecting its water distribution, which is important for the taste and texture of food.

[0076] 4. Thermal analysis

[0077] A differential scanning calorimeter was used to measure the thermal properties of the sample. 10 mg of the sample was weighed and sealed in an aluminum sealed pan, equilibrated at 5°C for 5 min, heated from 5°C to 80°C at 10°C / min, held for 5 min, and cooled to 5°C at 10°C / min. The results are shown in Table 1. Figure 6 .

[0078] As can be seen from the figure, in the biphasic amphiphilic gel, the enthalpy of the endothermic peak and the exothermic peak is positively correlated with the oil gel ratio, which is attributed to the increase in the concentration of the lipid structure phase in the biphasic amphiphilic gel. The oil gel is compared with the biphasic amphiphilic gel, and the results show that the incorporation of the oil gel into the hydrogel phase changes the thermal behavior of the oil gel, thereby changing its thermal properties. The shift of the endothermic peak and the exothermic peak of the biphasic amphiphilic gel indicates the effect of the hydrogel on thermal stability. In general, the thermal properties of the biphasic amphiphilic gel are different from those of the oil gel, which will provide a thermal performance reference for expanding its application in fat replacement.

[0079] 5. Internal interactions of gel structures

[0080] FT-IR spectroscopy was used to determine the interactions within the sample structure. The sample was dehydrated. The spectrum was scanned in the range of 4000-400 cm -1 , resolution 4cm -1 , the results are shown in Figure 7 .

[0081] FT-IR results show that the formation mechanism of the two-phase amphiphilic gel is based on the physical interaction between the oil gel and the hydrogel. In all two-phase amphiphilic gels, the infrared absorption peaks of the hydrogel and the oil gel were identified, and no new peaks or obvious displacements were detected, indicating that the two structural phases coexisted and no new chemical bonds were formed. The addition of pepper essential oil also did not cause changes in the chemical bonds. It can be seen that it is safe to replace traditional fats with two-phase amphiphilic gels.

[0082] 6. Crystal structure

[0083] The crystal structure of the samples was analyzed by X-ray diffractometer, and the X-ray radiation source was Cu Kα 40kV, 40mA, 25℃. Measured at 3.0° / min scan speed in the range of 5°-50°2θ. Calculate the interplanar spacing, see Figure 8 .

[0084] The results show that the prepared two-phase amphiphilic gel is a semi-crystalline solid with crystalline and amorphous components. The oleogel is a semi-crystalline solid with high crystallinity. The diffraction peaks are located at 19°, 21° and 23°. These peaks are characteristic of beeswax oleogel, indicating the presence of β, α and β′ crystals in the structure. The hydrogel has a wide hump-shaped structure near 20° and two sharp diffraction peaks at 36° and 45°. The broad peaks indicate its amorphous nature, and the sharp peaks indicate the presence of crystals or smectites. The XRD spectrum of the two-phase amphiphilic gel is close to that of the oleogel, and the diffraction pattern of the oleogel is better than that of the hydrogel. In addition, the addition of pepper essential oil has no significant effect on the crystal type and structure of the two-phase amphiphilic gel, further highlighting the value of pepper essential oil in improving mechanical properties.

[0085] 7. Microstructure

[0086] The gel sample was fixed in the sample holder with double-sided carbon tape, metallized, and its microstructure was observed by scanning electron microscopy. The distribution of oil gel and hydrogel in the sample was observed by CLSM. The sample was stained with Nile red and Nile blue. The argon laser excitation wavelengths were 488nm and 640nm respectively under 20x eyepiece magnification. The results are shown in Fig. 9 .

[0087] CLSM results show that the hydrogel is dispersed in the oil gel in the form of smaller droplets, and the oil gel presents a continuous phase. As the oil gel ratio increases, the gaps between the droplets become smaller, the biphasic amphiphilic gel network looks more compact, and the interaction between the droplets is stronger, thereby increasing the strength of its network and causing mechanical strength enhancement. From the SEM image, it can be seen that the oil gel does not form separate particles, but is interconnected and entangled in the protein network as part of the structure. The oil droplets are intertwined in the protein network, so that the biphasic amphiphilic gel has a large number of protrusions, representing the oil particles trapped in the gel network. The biphasic amphiphilic gel structure has a compact surface and very small gaps, indicating that it can ensure good uniformity in fat replacement applications.

[0088] 8. Rheological properties

[0089] The viscoelastic properties of the two-phase amphiphilic gel were evaluated using a DHR-1 rheometer equipped with parallel plates (diameter = 20 mm). During the test, about 2 g of sample was placed on the surface of the rheometer plate. First, a frequency sweep was performed in the frequency range of 0.1-100 Hz under a stress value of 0.1%. The storage modulus (G') and loss modulus (G") of the gel were recorded. The results are shown in Fig.10 .

[0090] The frequency scanning results show that the storage modulus (G') is greater than the loss modulus G", and there is no intersection between the two, indicating that a typical gel network has been formed and the gel has elastic characteristics similar to those of a solid. As the oil gel ratio increases, the G' and G" values ​​of the two-phase gel also increase, indicating that the oil gel network and the hydrogel network permeate each other, and a synergistic effect occurs when the hydrogel and oil gel are mixed. In addition, within the frequency scanning range of 1-100 Hz, as the scanning frequency increases, G' and G" do not decrease, but tend to increase, and the increasing trend of the 70:30 ratio gel is greater than that of the 90:10 formula, indicating that the formula with a relatively high hydrogel content has a higher viscosity and lower elastic properties.

[0091] 9. Storage stability

[0092] The gel was sealed and stored at 4°C for 2 months, and its water and oil binding capacity was tested on days 0, 10, 20, 30, 40, 50, and 60. The results are shown in Table 1. Fig.11 .

[0093] The results showed that the binding of the biphasic gel was significantly higher than that of the hydrogel. The binding force of the hydrogel decreased significantly after 5 days of storage, and deteriorated after 10 days of storage. The amphiphilic gel and oil gel had good storage stability. The binding force tended to be stable during the storage period of 1-60 days, without obvious slight decrease. The binding rate of the 70:30 formula without pepper essential oil decreased from 88.22% to 82.25%, and the 70:30 formula with pepper essential oil decreased from 88.54% to 82.32%. It can be seen that the amphiphilic gel has good storage stability.

[0094] In summary, the biphasic amphiphilic gel preparation process constructed by high-pressure homogenization combined with thermal induction in the present invention makes the mixed gel have good storage stability. It has been verified that the gel is stored at 4°C for 60 days without separation of the oil phase and the water phase, and the water-oil binding force is as high as 82.25% or more. From the appearance, the color of the biphasic amphiphilic gel prepared in the present invention is similar to that of the oil gel, which is creamy yellow; the test tube inversion experiment shows that there is no liquid flow, indicating that the self-supporting structure of the gel formed by the interweaving of the hydrogel and the oil gel is stable. The rheological properties test results show that the gel has obvious solid-like elastic characteristics. The gel can resist high-frequency scanning in the linear viscoelastic region and maintain good viscoelasticity and strength. The presence of myofibrillar protein hydrogel enhances the nutritional properties of the oil gel. 70% of the oil gel increases the maximum stress of the biphasic gel by 5.46 times and the Young's modulus by 3.15 times, which significantly improves the mechanical properties of the hydrogel. In addition, the addition of pepper essential oil greatly adjusted the mechanical properties of the oil gel. The maximum stress in the 70:30 formula with pepper essential oil was 170.15g, which was significantly less than 274.45g without pepper essential oil. It can be seen that under the premise of ensuring the protein content, the addition of trace pepper essential oil can significantly adjust the mechanical properties of the two-phase gel, and solid gels with adjustable mechanical properties can be produced according to demand. 22 The relaxation time decreased significantly, moving from 208.46 ms for the hydrogel to 106.46 ms. 21 and T 22 The peak area percentage of bound water increases with the increase of oil gel content, among which T 22 The area percentage increased from 86.45% for the hydrogel to 95.98% for the 90:10 formulation. 23 The content was significantly reduced, T 23 The percentage decreased from 11.17% for the hydrogel to 1.23% for the 90:10 formulation, indicating that the two-phase gel possessed good water binding capacity.

[0095] In addition, the storage stability of the two-phase gel is good. Within 60 days of storage, the binding rate of the 70:30 formula decreased from 88.22% to 82.25%, and the 70:30 formula containing pepper essential oil decreased from 88.54% to 82.32%, while the hydrogel deteriorated after 10 days of storage. The results of spectral analysis and structural characterization show that the two-phase amphiphilic gel is formed by the physical action between the hydrogel and the oil gel, without changing its original chemical properties, and the gel structure is tight and the water and oil are evenly distributed. It can be seen that the two-phase amphiphilic gel maintains the tight internal structure and good uniformity of the oil gel while enhancing the mechanical properties and nutritional properties, and has good storage stability. It has the potential to become a traditional fat substitute with high nutritional value, and can also be used in the field of separate or simultaneous delivery of fat-soluble and water-soluble functional factors.

[0096] Finally, a few points should be explained: Although the present invention has been described in detail above with general descriptions and specific embodiments, on the basis of the present invention, the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it; although the present invention has been described in detail with reference to the aforementioned embodiments, ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a biphasic amphiphilic gel with high mechanical properties based on myofibrillar protein and Zanthoxylum bungeanum essential oil, characterized in that: The following steps are involved: (1) Extracting myofibrillar protein; (2) preparing an oil gel containing Zanthoxylum bungeanum essential oil; (3) Preparation of myofibrillar protein hydrogel; (4) Preparation of two-phase amphiphilic gel.

2. The method for preparing a biphasic amphiphilic gel with high mechanical properties based on myofibrillar protein and Zanthoxylum bungeanum essential oil according to claim 1, characterized in that: The method for extracting myofibrillar protein in step (1) is as follows: cut fresh pork into small pieces and mash them, mix them with 4 volumes of pH = 7.0 phosphate buffer, homogenize them at 10000-12000 r / min for 1 min, filter, centrifuge at 2000-5000 r / min for 10 min, collect the precipitate to obtain crude myofibrillar protein, repeat twice, disperse the crude myofibrillar protein in 4 volumes of 0.1 M NaCl, homogenize them at 10000-12000 r / min for 1 min, centrifuge them at 2000-5000 r / min for 10 min, repeat twice, and obtain purified myofibrillar protein.

3. The method for preparing a biphasic amphiphilic gel with high mechanical properties based on myofibrillar protein and Zanthoxylum bungeanum essential oil according to claim 1, characterized in that: The preparation method of the oil gel containing Zanthoxylum essential oil in step (2) is as follows: adding Zanthoxylum essential oil to corn germ oil, magnetically stirring, and then adding oil gelling agent beeswax to the corn germ oil containing Zanthoxylum essential oil to obtain a mixture, magnetically stirring and heating the mixture to dissolve the oil gelling agent, cooling, and storing for a period of time to allow the oil gel to be completely formed.

4. The method for preparing a biphasic amphiphilic gel with high mechanical properties based on myofibrillar protein and Zanthoxylum bungeanum essential oil according to claim 3, characterized in that: The concentration of Zanthoxylum essential oil in corn germ oil is 0.2-0.4%, and the concentration of oil gelling agent beeswax in corn germ oil containing Zanthoxylum essential oil is 8-12%, and the concentration unit is g / mL.

5. The method for preparing a biphasic amphiphilic gel with high mechanical properties based on myofibrillar protein and Zanthoxylum bungeanum essential oil according to claim 3, characterized in that: The magnetic stirring speed is 300-500 r / min, and the magnetic stirring time is 30-60 min; the heating temperature is 130-145°C, the storage temperature is 23~27°C, and the storage time is 24 h.

6. The method for preparing a biphasic amphiphilic gel with high mechanical properties based on myofibrillar protein and Zanthoxylum bungeanum essential oil according to claim 1, characterized in that: The preparation method of the myofibrillar protein hydrogel in step (3) is as follows: the myofibrillar protein prepared in step (1) is dispersed in a phosphate buffer solution to a concentration of 40-60 mg / mL, high-speed homogenized at 10000-12000 r / min for 40-80 s, centrifuged at 3000-4000 r / min for 3-5 min, equilibrated at room temperature for 20-40 min, equilibrated in a water bath at 80-85°C for 30-40 min, and then immediately cooled to obtain the myofibrillar protein hydrogel, which is stored at 4°C, wherein the water bath heating rate is 1-2°C / min.

7. The method for preparing a biphasic amphiphilic gel with high mechanical properties based on myofibrillar protein and Zanthoxylum bungeanum essential oil according to claim 1, characterized in that: The preparation method of the two-phase amphiphilic gel in step (4) is as follows: the oil gel prepared in step (2) is heated and solubilized, cooled, and then mixed with the myofibrillar protein hydrogel prepared in step (3), homogenized, placed in a cylindrical mold, heated in a water bath, cooled in an ice water bath, and stored at 4° C. to obtain a two-phase amphiphilic gel.

8. The method for preparing a biphasic amphiphilic gel with high mechanical properties based on myofibrillar protein and Zanthoxylum bungeanum essential oil according to claim 7, characterized in that: In step 4), the solubilization temperature is 70-80°C, the oil gel cooling temperature is 60-65°C, the volume ratio of oil gel to hydrogel is (70-90): (10-30), the homogenization speed is 10000-12000 r / min, the homogenization time is 40-60s, the water bath temperature is 80-85°C, the water bath heating time is 30-40 min, the water bath heating rate is 1-2°C / min, and the ice water bath cooling time is 30-35 min.

9. A two-phase amphiphilic gel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the two-phase amphiphilic gel according to claim 9 in replacing fat.